Structural and genomic evolutionary dynamics of Omicron variant of SARS-CoV-2 circulating in Madhya Pradesh, India - Dhankher, Suman; Yadav, Pooja; Sharma, Shashi; Gupta, Ekta; Yadav, Ram Govind; Dash, Paban Kumar; Parida, Manmohan (Frontiers in Medicine, 2024)
The SARS-CoV-2 Omicron (B.1.1.529) variant emerged in early November 2021 and its rapid spread created a fear worldwide. This was attributed to its increased infectivity and escaping the immune mechanisms. Spike protein of Omicron has more mutations (>30) than any other previous variants and was declared as the variant of concern (VOC) by WHO. The concern amongst the scientific community was huge about this variant and an updated information on circulating viral strains is important in order to better understand the epidemiology, virus pathogenicity, transmission, therapeutic interventions and vaccine development. A total of 710 samples were processed for sequencing and identification upto a resolution of sub-lineage. The sequence analysis revealed Omicron variant with distribution as follows B.1.1 , B.1.1.529, BA.